Double B-type magnetic integrated transformer based input-parallel output-parallel LLC resonant converter modules - Xia, Nenghong; Yan, Shuang; Ma, Huaqi; Mao, Xike; Chen, Mengqi (Frontiers in Energy Research, 2024)
The LLC resonant converter used in high-power situations suffers from the problems of high conduction loss and current stress, which can be solved using input-parallel-output-parallel (IPOP) connected converter modules. However, this leads to a multiple increase in the number of magnetic components, which reduces the power density. Magnetic integration technology is an effective way to reduce the volume of converters. Currently, the magnetic integrated transformer based on EE type cores is widely used to realize miniaturization, and uses the leakage inductance instead of resonant inductance to improve the power density. However, the leakage inductance is difficult to control, and the external radiated magnetic field will produce serious eddy current loss and electromagnetic interference. This paper proposes a novel double B-type magnetic integrated transformer, which can integrate the magnetic components of two LLC resonant converters simultaneously and where the resonant inductances are wound independently. The structure contains four low reluctance branches, which are used as the cores of the transformer and the resonant inductance, respectively. The decoupling integration method, which integrates the four components into a single core, has been used to increase core utilization and improve the power density. On this basis, the transformer's high and low voltage windings are cross-arranged to reduce the magnetic field intensity in space, further decreasing the loss and electromagnetic interference. Compared with the EE type magnetic integrated transformer, the volume of the proposed structure is reduced by 5.9%. A 400W experimental prototype is built, and the results verify the validity of the design. Parallel (IPOP) to apply in high-power conditions can solve all the abovementioned problems [8]. However, this also causes a considerable increase in power converters. The weight and volume of magnetic components such as inductances and transformers account for about 30% to 40% of the whole [9], which become the main constraints on improving efficiency and power density. Magnetic integration technology effectively improves power density by structurally concentrating multiple discrete magnetic components on a single core without affecting regular operation.